Who has been hit hardest by South Africa’s lockdown? We found some answers - Arndt, Channing; Robinson, Sherman; Gabriel, Sherwin (2020)
In trying to limit the spread of COVID-19, policymakers globally have the difficult task of balancing the positive health effects of lockdowns against their economic costs, particularly the burdens lockdowns impose on low-income and food-insecure households. In the case of South Africa, the lockdown policies are relatively stringent, and the economic impacts large.